Fertilization Induced Soil Microbial Shifts Show Minor Effects on Sapindus mukorossi Yield - Juntao Liu; Zhexiu Yu; Yingyun Gong; Jie Chen; Ling Zhou; Weihua Zhang; Liming Jia (Microorganisms)
Fertilization can improve soil nutrition and increase the yield of Sapindus mukorossi, but the response of soil microbial communities to fertilization treatments and their correlation with soil nutrition and Sapindus mukorossi yield are unclear. In order to investigate the characteristics of soil physicochemical qualities and the bacterial community, we carried out a field experiment comparing various quantities of nitrogen (N), phosphorus (P), and potassium (K) fertilizers to the unfertilized control treatments and the yield of Sapindus mukorossi in raw material forests in response to different applications of fertilizers and to try to clarify the interrelation among the three. Results showed that (1) there are significant differences in the effects of different fertilization treatments on the soil properties of Sapindus mukorossi raw material forests. The increase in the application rates of nitrogen or phosphorus fertilizers significantly reduced the soil pH value. (2) Compared with control, the α-diversity of bacterial communities was significantly lower in N3P2K2 and N1P1K2 treatments. Among the dominant groups of soil bacteria at the phylum level, the relative abundance of Chloroflexi showed an increase and then a decrease trend with the increase in N application. The relative abundance of Firmicutes, Bacteroidota, and Fusobacteriota was positively correlated with the application of P and K fertilizers, while the relative abundance of Acidobacteriota and Verrucomicrobiota decreased with the increase in P and K fertilizers. (3) The N2P2K2 treatment produced the highest sapindus yield (1464.58 kg/ha), which increased by 258.67% above the control. (4) Redundancy analysis (RDA) showed that the primary determinants of bacterial community structure were soil pH, total K, and effective P concentration. (5) Structural equation modeling (SEM) showed that soil nutrient content was the main direct factor driving the yield of Sapindus mukorossi, whereas the bacterial community attributes (e.g., diversity and structure) had minor effects on the yield. In summary, the rational use of formulated fertilization can change the bacterial community structure, improve the bacterial diversity, and increase the soil nutrient content, with the latter exerting a significant effect on the improvement of the yield of Sapindus mukorossi.